2015
DOI: 10.1002/jmv.24297
|View full text |Cite
|
Sign up to set email alerts
|

Three infants with rotavirus gastroenteritis complicated by severe gastrointestinal bleeding

Abstract: Rotavirus gastroenteritis causes substantial morbidity and mortality worldwide in children. We report three infants with rotavirus gastroenteritis complicated by various severity of gastrointestinal bleeding. Two patients (cases 1 and 2) recovered completely without any specific treatments. One patient (case 3) died despite extensive treatments including a red blood cell transfusion and endoscopic hemostatic therapy. Rotavirus genotypes G1P[8] and G9P[8] were detected in cases 2 and 3, respectively. Rotavirus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Rotavirus diarrhea disease and mortality is a recurrent enigma. In consonant with the findings of Yoshiki et al, 28 the observed severe, non-bloody, non-copious, non-foamy watery diarrhea, vomiting, loss of skin turgor, sunken eyes, weakness, and coma presumptively pointed to viral diarrhea in the participants. Several workers have submitted that rotavirus infections were often severe, while some children passed on subsequently due to improper management of the diarrhea.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Rotavirus diarrhea disease and mortality is a recurrent enigma. In consonant with the findings of Yoshiki et al, 28 the observed severe, non-bloody, non-copious, non-foamy watery diarrhea, vomiting, loss of skin turgor, sunken eyes, weakness, and coma presumptively pointed to viral diarrhea in the participants. Several workers have submitted that rotavirus infections were often severe, while some children passed on subsequently due to improper management of the diarrhea.…”
Section: Discussionsupporting
confidence: 89%
“…Gel electropherogram of seminested multiplex polymerase chain reaction products of rotavirus VP4 P-typing showing 267 bp depicting P[6] genotype, using primer set C for samples 04, 05, 08, 15 (the mortality case),16,18,21,27,28, 39, and negative control. The mortality case is shown with a red star while other critical cases are indicated by yellow star on top of the respective sample well.…”
mentioning
confidence: 99%
“…Literature search found 6 English-language full reports (14 cases) [ 3 , 5 9 ], 7 Japanese-language full reports (10 cases) [ 10 – 16 ], of which 4 reports included English abstracts [ 10 , 13 , 14 , 16 ], and 10 Japanese-language abstract-only reports (12 cases) [ 17 – 26 ]. Of the 36 cases reported, the site of the bleeding lesion was not confirmed by endoscopy in the 2 cases with RV gastroenteritis [ 9 ]. However, because the site of the bleeding lesion in these patients appeared to be upper gastrointestinal tract, these 2 cases were included for analysis in the study.…”
Section: Resultsmentioning
confidence: 99%
“…Gastric ulcer also occurred in 1 NoV case. In the remaining 2 RV cases, the site of the bleeding lesion was not confirmed by endoscopy, but it appeared to be in the upper gastrointestinal tract [ 9 ]. The site of ulcer was the bulbus of the duodenum in all but 1 with the posterior wall of the stomach.…”
Section: Resultsmentioning
confidence: 99%
“…Gastrointestinal bleeding and urinary stone that may cause post-renal renal failure are also considered to be severe complications of RV gastroenteritis. 11,12,21 Similar to RV-associated encephalitis/encephalopathy, 2-4 most of the complications, in particular, urinary stone, have been reported from Japan. 9,10 Given that urinary stone or GI bleeding occur rarely in RV gastroenteritis, not only pathogenesis but also the precise incidence of the complications remain unclear.…”
Section: Discussionmentioning
confidence: 92%